KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATEMATIKA BERDASARKAN LANGKAH - LANGKAH PEMECAHAN MASALAH POLYA - Nur Aini Fitri; M. Imamuddin; Isnaniah Isnaniah; Haida Fitri (EDU RESEARCH, 2024)
This research is motivated by the test results at SMPN 7 Tualang, students who have difficulty solving math story problems. Students have difficulty in understanding the problem, students have difficulty in planning problem solving in the problem, students have difficulty in completing the planning in the problem, and students have difficulty in stating the final result. Based on these conditions, researchers are interested in conducting research by taking the formulation of the problem is how the form of difficulties faced by students in solving math story problems based on Polya's problem solving steps. The purpose of this research is to describe students' difficulties in solving math story problems based on Polya's problem solving steps in Class VIII.2 SMP N 7 Tualang. This type of research is descriptive quantitative. The subjects in the study were students totaling 29 students, data collection techniques using a description test of 3 questions. Data analysis techniques used are data reduction, data presentation and conclusion drawing. Based on the results of the analysis of data collection techniques using written tests, the results of the research that has been done are that many students have difficulty in solving math story problems using Polya's steps, including 45.40% of students who find it difficult to understand story-shaped problems, 48.65% of students who find it difficult to plan problem solving in math problems, 61.68% of students who find it difficult to solve problems in math problems, 23.13% of students who find it difficult to state the final result. Based on these findings, it is hoped that students can study harder by increasing practice working on math problems in story form.